2012
DOI: 10.7150/ijms.4768
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Oxidative DNA Damage, Oxidative Stress and Coenzyme Q10 in Patients with Coronary Artery Disease

Abstract: The correlation of coronary artery disease (CAD) with pro-oxidant/antioxidant balance and oxidative DNA damage was investigated.Seventy-seven patients with CAD and 44 healthy individuals as control were included in this study. The comparative ratios of ubiquinol-10/ubiquinone-10, 8-hydroxy-2'-deoxyguanosine/deoxyguanosine and the level of MDA measured by HPLC and the activities of GPX and SOD by colorimetric approach in blood samples obtained from patients with CAD were unraveled.8-OHdG/dG ratios, serum MDA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
4
45
0
2
Order By: Relevance
“…The study of Fazeli et al, in seminal plasma also indicated that increase in MDA level was invariably followed by a decrease in the level of TAC 30 . Moreover, in clinical study was done by Kaya et al., in patients with coronary artery disease also showed an inverted correlation between 8-OHdG and MDA level and ubiquinol-10/ubiquinone-10 ratio respectively 31 . Interestingly, in Kaya study aside from a positive correlation between 8-OHdG and MDA, a positive correlation also happened between 8-OHdG with GPx level.…”
Section: Discussionmentioning
confidence: 88%
“…The study of Fazeli et al, in seminal plasma also indicated that increase in MDA level was invariably followed by a decrease in the level of TAC 30 . Moreover, in clinical study was done by Kaya et al., in patients with coronary artery disease also showed an inverted correlation between 8-OHdG and MDA level and ubiquinol-10/ubiquinone-10 ratio respectively 31 . Interestingly, in Kaya study aside from a positive correlation between 8-OHdG and MDA, a positive correlation also happened between 8-OHdG with GPx level.…”
Section: Discussionmentioning
confidence: 88%
“…6 Also, clinical and experimental studies have shown that disturbing oxidant-antioxidant balance system is involved in the pathogenesis of chronic diseases such as cancer, 7 coronary heart disease, diabetes, liver injury and kidney injury. [8][9][10] Antioxidant and antioxidative enzyme activities reduce due to GM or increase of lipid peroxidation products. 11 Most research studies against GM -induced nephrotoxicity are focused on the use of various anti-oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…A number of lines of evidence suggest that an altered oxidantantioxidant imbalance is associated with CAD [15]. Other studies have also revealed an elevated oxidative stress and reduce of plasma SOD and GPx in CAD patients [18] [19]. Moreover, several studies have demonstrated that GPx-3 deficiency has been associated with cardiovascular disease [20] [21], although its role in transcriptional level remained unknown [10].…”
Section: Discussionmentioning
confidence: 99%